The roles and mechanisms of epigenetic regulation in pathological myocardial remodeling - Zhao, Kun; Mao, Yukang; Li, Yansong; Yang, Chuanxi; Wang, Kai; Zhang, Jing (Frontiers in Cardiovascular Medicine, 2022)
Pathological myocardial remodeling was still one of the leading causes of death worldwide with an unmet therapeutic need. A growing number of researchers has addressed the role of epigenome changes in cardiovascular diseases, paving the way for the clinical application of novel cardiovascular-related epigenetic targets in the future. In this review, we summarized the emerged advances of epigenetic regulation, including DNA methylation, Histone posttranslational modification, Adenosine disodium triphosphate (ATP)-dependent chromatin remodeling, Non-coding RNA, and RNA modification, in pathological myocardial remodeling. Also, we provided an overview of the mechanisms that potentially involve the participation of these epigenetic regulation.